1988
DOI: 10.1002/arch.940080207
|View full text |Cite
|
Sign up to set email alerts
|

Neuroparsin: A new energetic neurohormone in the African locust

Abstract: The effects of neuroparsins on hemolymph trehalose and lipid levels and o n total glycogen content were analyzed in Locusta migratoria. Saline and methanol extracts of the two lobes of the corpora cardiaca were assayed. Neuroparsins (A and B) were demonstrated to be hypertrehalosemic and hyperlipemic proteins of the neural lobe. Both of these metabolic activities of neuroparsins were somewhat less potent than those of adipokinetic hormone (AKH). Neuroparsin activity could be distinguished from AKH by blockage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…There have been other effects described to locust neuroparsin, there is notably a large number of papers on its anti-diuretic effects, however the bioassay used did not survive scrutiny and the doses needed for these effects also seem unphysiologically high (see Coast et al, 2002), whereas its hyperlipemic and hyperglycemic effects (Moreau et al, 1988) have never been confirmed.…”
Section: Introductionmentioning
confidence: 95%
“…There have been other effects described to locust neuroparsin, there is notably a large number of papers on its anti-diuretic effects, however the bioassay used did not survive scrutiny and the doses needed for these effects also seem unphysiologically high (see Coast et al, 2002), whereas its hyperlipemic and hyperglycemic effects (Moreau et al, 1988) have never been confirmed.…”
Section: Introductionmentioning
confidence: 95%
“…Purified using the same procedure, they were previously demonstrated to have antidiuretic [2], hyperglycemic and hyperlipemic [3] and antigonadotropic [l l] actions. We demonstrate that all these activities are triggered by a single molecule; the neuroparsins are obviously polytropic locust neurohormones as it is of common occurrence with most neuropeptides of both invertebrates and vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…These two proteins are produced by the Al type of protocerebral median neurosecretory cells [ 11. They are multifunctional neurohormones: they inhibit the effects of juvenile hormone [I], stimulate fluid reabsorption of isolated recta [2] and induce an increase in hemolymph lipid and trehalose levels [3].…”
mentioning
confidence: 99%
“…is not tightly linked to the control of reproduction in gregarious locusts, but may perhaps be involved in other physiological functions. These may relate to some of the biological activities previously reported for Lom-NP (e.g., hypertrehalosemic or neuritogenic effects) (Moreau et al, 1988;Vanhems et al, 1990).…”
Section: Introductionmentioning
confidence: 93%